Feasibility Analysis for Economic Flyover in Bojonegoro District - Dewa Yanto, Putra; Heka Ardana, Putu Doddy; adamy, Marbawi (Department of Information Technology, Universitas Malikussaleh, Aceh Utara, Indonesia, 2023)
The traffic jam that occurred in the city of Bojonegoro on the Rajekwesi – MT road section. Haryono, the leading cause of problems in the area, is at intersections and meetings with railroad tracks. Building a flyover is one solution to congestion that occurs at railroad crossings. An economic feasibility study must be carried out to assess the characteristics of a development project. This study aims to determine how much profit and costs are obtained and the extent of its economic feasibility. The project that will be examined in this study is the construction of a flyover in Bojonegoro district. Then, the feasibility of the Flyover construction project is based on the calculation of Net Present Value (NPV), Benefit Cost Ratio (BCR), and Internal Rate of Return (IRR). The results of this economic feasibility analysis There are three alternative route selection that are associated with economic feasibility where the first alternative with NPV: 2,121,743,718,000, BCR: 12.7499 and IRR: 57 then the second alternative with NPV value: 1,733,795,057,000, BCR: 10.3771, IRR: 50% and the third alternative with an NPV value: 1,395,424,941,000, BCR: 6,978 and IRR: 37%. Based on the economic feasibility analysis using process hierarchy analysis, the first alternative was chosen with a score of 0.571. With the construction of the flyover, it is hoped that it can break up the flow of traffic on the Bojonegoro - Cepu - Nganjuk section to encourage economic growth, trade, and regional development in the Bojonegoro district.